2019
DOI: 10.1051/epjconf/201919701001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of H.E.S.S. Lidar profiles on Crab Nebula data

Abstract: The H.E.S.S. experiment in Namibia is a high-energy gamma-ray telescope sensitive in the energy range from 30 GeV to a several tens of TeV, that uses the atmospheric Cherenkov technique to detect showers developed within the atmosphere. The elastic lidar, installed on the H.E.S.S. site, allows to reduce the systematic errors related to the atmospheric composition uncertainties thanks to the estimation of the extinction profile for the Cherenkov light (300-650 nm). The latter has a direct impact on the reconstr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 6 publications
1
18
0
Order By: Relevance
“…Therefore, atmospheric conditions are monitored during data taking in experiments such as H.E.S.S. (Aharonian et al, 2004;Devin et al, 2019), MAGIC (Aleksić et al, 2012) and VERITAS (Weekes et al, 2002;Holder et al, 2011). Additional instruments to measure the transparency of the atmosphere are also planned to be built for CTA (Doro et al, 2013;López et al, 2013;Gaug, 2016;Iarlori et al, 2016;Valore et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, atmospheric conditions are monitored during data taking in experiments such as H.E.S.S. (Aharonian et al, 2004;Devin et al, 2019), MAGIC (Aleksić et al, 2012) and VERITAS (Weekes et al, 2002;Holder et al, 2011). Additional instruments to measure the transparency of the atmosphere are also planned to be built for CTA (Doro et al, 2013;López et al, 2013;Gaug, 2016;Iarlori et al, 2016;Valore et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…H. Abdalla 1 , H. Abe 2 , S. Abe 2 , A. Abusleme 3 , F. Acero 4 , A. Acharyya 5 , V. Acín Portella 6 , K. Ackley 7 , R. Adam 8 , C. Adams 9 , S.S. Adhikari 10 , I. Aguado-Ruesga 11 , I. Agudo 12 , R. Aguilera 13 , A. Aguirre-Santaella 14 , F. Aharonian 15 , A. Alberdi 12 , R. Alfaro 16…”
Section: Acknowledgementsmentioning
confidence: 99%
“…An approach to atmospheric corrections for IACTs has been already studied in MAGIC [8] and H.E.S.S. [5,9] collaborations. In [8] it is shown that for layers of low and moderate optical depths a straightforward correction to the reconstructed energy is possible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is caused mainly by the uncertainty in the atmospheric production and absorption of the Cherenkov photons as well as lack of a "test Email addresses: jsitarek@uni.lodz.pl (Julian Sitarek), dsobczynska@uni.lodz.pl (Dorota Sobczyńska), kadamczyk@uni.lodz.pl (Katarzyna Adamczyk), mitsza@camk.edu.pl (Michał Szanecki) beam" for IACT instruments. Despite various calibration methods (inter-telescope calibration : Hofmann, 2003, muon analysis: Vacanti et al, 1994, flux comparisons at different thresholds: Aleksić et al, 2016b, LIDAR corrections: Fruck & Gaug, 2015Devin et al, 2019) it is still at the level of ∼ 15% (see e.g. Aharonian et al, 2006;Abeysekara et al, 2015;Aleksić et al, 2016b), much larger than of satellite experiments (c.f.…”
Section: Introductionmentioning
confidence: 99%